2012
DOI: 10.5858/arpa.2011-0673-oa
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Histologic Assessment and Fluorescence In Situ Hybridization Using MelanoSITE in Evaluation of Histologically Ambiguous Melanocytic Lesions

Abstract: N Context.-The 4-probe, multicolor, fluorescence in situ hybridization (FISH) panel targeting chromosomes 6 and 11 has shown promising sensitivity and specificity in distinguishing between benign nevi and malignant melanoma. Only a few studies have assessed the potential utility of FISH in classification of histologically ambiguous melanocytic lesions. In the United States, this assay is exclusively licensed to NeoGenomics Laboratories (Irvine, California), which provides the technical component and has develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
(42 reference statements)
4
21
0
4
Order By: Relevance
“…While it can be argued that some of the cases with negative molecular results that were interpreted as malignant may not be considered true melanomas in the absence of outcome data, it is also possible that a small subset of 'bona fide' melanomas lacks the usual molecular alterations present in most lesions and detectable by the current molecular methods (FISH or gene expression score). These observations are in line with the findings of previous reports 17,19,25 that expert histopathologic evaluation has a higher sensitivity and specificity than any currently available ancillary test for the diagnosis of melanocytic lesions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While it can be argued that some of the cases with negative molecular results that were interpreted as malignant may not be considered true melanomas in the absence of outcome data, it is also possible that a small subset of 'bona fide' melanomas lacks the usual molecular alterations present in most lesions and detectable by the current molecular methods (FISH or gene expression score). These observations are in line with the findings of previous reports 17,19,25 that expert histopathologic evaluation has a higher sensitivity and specificity than any currently available ancillary test for the diagnosis of melanocytic lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Within the challenging cases, the sensitivity was lower for spitzoid lesions than for nevoid ones (50% vs 62%). Overall, these results are comparable to those of previous reports showing a significant decrease in FISH sensitivity and less so in specificity for histopathologically ambiguous 16,17,19,24,25 In an effort to preserve uniformity, FISH results obtained with 6q23/CEP6 probes, used as part of the protocol at two of the three institutions, were not reported in this study. However, it is worth mentioning that a few cases, including some 'false-negative' ones, showed FISH abnormalities only by the 6q23/CEP6 criterion, thus potentially further raising the sensitivity of a full 7-probe FISH format in the unequivocal group (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…In both cases, the naevi were reported as architecturally aberrant but with no evidence of malignancy, with advice to careful follow-up. Tetraploidy has been detected in skin naevi on FISH testing and is often a source of false positivity in FISH analysis of melanocytic lesions 8 9. The presence of tetraploid cells is readily identifiable as the increased signal pattern affects all probes in FISH panel.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was most It is important to note that the presence of tetraploidy in nevi can cause a false-positive FISH result. Zembowicz et al 45 prospectively analyzed 140 lesions, and found that 27% of abnormal FISH results were false-positive results because of tetraploidy. After correcting for known false-positive results, all lesions considered atypical nevi had normal FISH signals.…”
Section: J Am Acad Dermatolmentioning
confidence: 97%